A Case Study On Nestle - Hamidon, Syazrah (2005)
Nestle is one of the oldest and largest food and beverage (F&B) company in the world. This fact alone warrants the need for this case study, which covers the period from its inception till today. The case study touches on its illustrious history, business philosophy, corporate business principles and policies and working through its various products, financials, organization structure and business processes.